2013
DOI: 10.1166/jctn.2013.3160
|View full text |Cite
|
Sign up to set email alerts
|

Spin Polarization of Electrons in Metallohedral B24N24 Nanocage: A Density Functional Theory Investigation

Abstract: First principles calculations based upon density functional theory (DFT) with the spin polarized generalized gradient approximation (SGGA) have been performed to study the spin polarization phenomenon induced by inserting light metals (Li, Na, K, Mg, Ca and Al) into the B 24 N 24 nanocage. The obtained binding energies show that Al and K atoms being incorporated into the B 24 N 24 nanocage can form most stable complexes while other metals might form unstable complex with positive binding energy. Spin polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…[22][23][24] In our study of beryllium substituents planar tetracoordinate carbon materials, 25 we found that the calculation results given by the B3LYP method 26 27 were in good agreement with those given by MP2 calculations. 28 The differences in geometries between the two levels are small, the symmetry of the structures are the same for MP2 and B3LYP results.…”
Section: Methodsmentioning
confidence: 68%
“…[22][23][24] In our study of beryllium substituents planar tetracoordinate carbon materials, 25 we found that the calculation results given by the B3LYP method 26 27 were in good agreement with those given by MP2 calculations. 28 The differences in geometries between the two levels are small, the symmetry of the structures are the same for MP2 and B3LYP results.…”
Section: Methodsmentioning
confidence: 68%
“…[27][28][29] Therefore, the DFT (B3LYP 30 31 ) method was selected in the present work. All reported structures were optimized and characterized as minima at the B3LYP/6-311+G(d, p) level.…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28] In this work, the B3LYP 29 30 functional was employed for all calculations. The structures of all of the studied silicon-doped boranes were optimized and characterized as minima at the B3LYP/ 6-311 + G(d, p) level.…”
Section: Methodsmentioning
confidence: 99%